Mixed Methods Analysis of Caregiver Satisfaction With the Early Autism Evaluation Hub System - Ann Marie Martin PhD; Jordan Huskins MD; Angela Paxton BS; Amira Nafiseh MD, MPH; Mary R. Ciccarelli MD; Brandon Keehn PhD; Rebecca McNally Keehn PhD (Journal of Patient Experience)
Community-based methods for autism evaluation may be one solution for ameliorating delays in diagnosis, which are exacerbated for children from minoritized backgrounds. However, limited research has examined caregiver satisfaction with community-based models of autism evaluation. Thus, our objective was to use a mixed-methods approach to investigate caregiver satisfaction with their child's autism evaluation conducted across a statewide system of primary care autism diagnosis. Results indicated overall high satisfaction and no significant differences were found between satisfaction total scores nor caregiver stress and any child/family demographic variables. Satisfaction and stress were also not related to autism diagnostic outcome, clinician diagnostic certainty, or diagnostic accuracy. Qualitative suggestions for evaluation improvement include more thorough explanation of diagnosis and service recommendations. Overall, our findings indicate high caregiver satisfaction with multiple dimensions of community-based autism evaluation in the primary care setting, suggesting this may be a feasible and sustainable model that caregivers find acceptable.